Developing morphological knowledge with online corpora in an ESL vocabulary classroom - Zhang, Rui (Frontiers in Psychology, 2022)
Morphology is the study of word forms and the ways in which words are varied and related to other words in a language. It has been regarded as an essential discipline that is indispensable in language acquisition. It helps learners to figure out the word structure and meaning, particularly the meaning changing of morphemes, which is pivotal for defining words. The present study focuses on developing morphological knowledge with online corpora, useful tools for teaching and learning the changes happened in English. Given this light, this research reports an ESL vocabulary classroom in which the instructor designs vocabulary classroom activities with COCA, BNC, TIME MAGAZINE corpus to enrich students’ English vocabulary knowledge, help them master word usage, and foster their corpus literacy. This study is oriented by the framework of classroom action research (CAR). Students’ classroom performances were recorded and their self-reflections of learning experiences were collected for thematic analysis. The results indicate that, firstly, students’ morphological knowledge has been developed as well as their vocabulary knowledge; secondly, their vocabulary self-regulated learning motivation has been incentivised that they are able to answer their own queries about words; thirdly, students’ corpus literacy has been fostered, which facilitates their ongoing vocabulary learning; last but not least, a community of inquiry has been established in which students collaborate to construct vocabulary knowledge. The study has wider implications for constructing the student-centered vocabulary classroom and implementing corpus-based instruction in other second language vocabulary classrooms.